2019
DOI: 10.1371/journal.pone.0217293
|View full text |Cite
|
Sign up to set email alerts
|

Classification of skin lesions using transfer learning and augmentation with Alex-net

Abstract: Skin cancer is one of most deadly diseases in humans. According to the high similarity between melanoma and nevus lesions, physicians take much more time to investigate these lesions. The automated classification of skin lesions will save effort, time and human life. The purpose of this paper is to present an automatic skin lesions classification system with higher classification rate using the theory of transfer learning and the pre-trained deep neural network. The transfer learning has been applied to the Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
145
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(149 citation statements)
references
References 33 publications
1
145
0
3
Order By: Relevance
“…Some excellent studies [15]- [18] have shown that there is considerable redundancy in a traditional VGG model, and layer-by-layer connections make the network replicate features of the front layer in the whole network. Hosny et al [19], [20] performed several experiments using different models, such as Alex-net, ResNet, VGG, and GoogleNet. Their results showed that the VGG model required substantial memory and high-configuration hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Some excellent studies [15]- [18] have shown that there is considerable redundancy in a traditional VGG model, and layer-by-layer connections make the network replicate features of the front layer in the whole network. Hosny et al [19], [20] performed several experiments using different models, such as Alex-net, ResNet, VGG, and GoogleNet. Their results showed that the VGG model required substantial memory and high-configuration hardware.…”
Section: Introductionmentioning
confidence: 99%
“…Since the image processing techniques were developed, Computer-Aided Detection (CAD) systems and approaches in the classification [ 3 , 4 , 5 , 6 , 7 ] and segmentation [ 8 ] of a Pigmented Skin Lesion (PSL) have been improved, benefiting patient diagnoses in early stages of the disease without shocking or painful medical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The main point of CNN is that it is able to map important features of images that can be used to classify those images without the CNN's being explicitly programmed to do so. CNN has been proven to work with great accuracy in the classification of many medical domains like diabetic retinopathy detection and classification [4,5], Alzheimer's disease detection [6,7], and skin lesion detection [8,9], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The medical field could benefit a lot from the usage of CNN for image classification, but the main drawback is the number of images available for training, and that is where transfer learning can be used. Using transfer learning for medical images has been successfully applied in References [4,6,8]. As pointed out by Chollet [15] , transfer learning uses two main techniques: fine-tuning, wherein the original weights will be re-tuned to suit the new dataset, or feature extraction, in which the original weights will be fixed and the original layers will serve for feature extraction only.…”
Section: Introductionmentioning
confidence: 99%